2009
DOI: 10.1016/j.aprim.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Cooperación entre atención primaria y servicios de salud mental

Abstract: The cooperation between the PC and the specialised mental health services of Catalonia is optimal in some aspects, but patient waiting time needs to be reduced for first visits to the AMHC and training activities offered by the CAMHC and the ACT need to be increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
2
0
4
Order By: Relevance
“…We found that mental health team visits to PCCs usually occurred 3 or more times a month and training visits took place once a month. In 92.4% of cases communication between the CMHU and GP was rated at as good or very good; in a similar study carried out in Catalonia cooperation between primary care and specialist services in mental health was considered satisfactory [ 24 ]. These results contrast with a report that French GPs thought there was a lack of communication between mental health services and primary care services [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that mental health team visits to PCCs usually occurred 3 or more times a month and training visits took place once a month. In 92.4% of cases communication between the CMHU and GP was rated at as good or very good; in a similar study carried out in Catalonia cooperation between primary care and specialist services in mental health was considered satisfactory [ 24 ]. These results contrast with a report that French GPs thought there was a lack of communication between mental health services and primary care services [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research performed in the Netherlands revealed similar trends: GPs’ diagnoses of mental health problems decreased and their referral to secondary care increased from 1987 to 2001 [ 11 ]. Such findings indicate a real need to build GPs’ skills in the assessment and management of mental health disorders [ 12 ] and to improve GPs’ collaboration with mental healthcare teams in general and psychiatrists in particular [ 13 , 14 ]. However, increased referral of mentally ill patients by GPs to secondary health care could also reflect the peculiarities of the mental healthcare sector in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados de la experiencia piloto «AP-SM Depresión» muestran la factibilidad y los efectos positivos de un proyecto colaborativo promovido desde AP y SM, con aportaciones respecto de estudios previos en nuestro medio12, 13, 15, 16, como la integración de intervenciones sobre diferentes áreas de colaboración, el enfoque pluridisciplinario y participativo, los datos poblacionales y el importante número de profesionales implicados.…”
Section: Discussionunclassified
“…En este caso, se utilizó como indicador comparativo el de los Contratos Programa y de Gestión Clínica vigentes: paroxetina + fluoxetina + citalopram + sertralina/antidepresivos totales salvo inhibidores de la monoaminooxidasa y tricíclicos. También se elaboró una encuesta adaptada de cuestionarios previos12, 26, que fue distribuida al comienzo y al final del periodo piloto del 2013 para conocer las valoraciones de los profesionales sobre los distintos ejes de intervención y sus efectos en la carga de trabajo asistencial, las interrelaciones con el equipo promotor y las expectativas de futuro (anexo).…”
Section: Materials Y Métodosunclassified
See 1 more Smart Citation